2006
DOI: 10.4103/0028-3886.24710
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical open mini uniskin incision technique in the surgical treatment of carpal tunnel syndrome

Abstract: In this clinical study we used a modified skin incision (mini uni-skin incision) technique in the surgical treatment of carpal tunnel surgery. Our results revealed that mini uni-skin incision is superior from the standard incision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…The recurrent thenar branch of the median nerve is also at risk for possible anatomical variations. In addition, palmar arteries, especially the superficial palmar arc, may be injured (2,9). No damage to these structures occurred in any of the patients in our study.…”
Section: Discussionmentioning
confidence: 69%
“…The recurrent thenar branch of the median nerve is also at risk for possible anatomical variations. In addition, palmar arteries, especially the superficial palmar arc, may be injured (2,9). No damage to these structures occurred in any of the patients in our study.…”
Section: Discussionmentioning
confidence: 69%
“…5) Several modifications regarding the length, location, and shape of the incision for OCTR have been reported. 5963) …”
Section: Treatmentmentioning
confidence: 99%
“…Idiopathic carpal tunnel syndrome is the commonest one of the many entrapment neuropathies encountered by neurosurgeons in Egypt and all over the world. It was reported that idiopathic carpal tunnel syndrome accounts for more than 200,000 surgical procedures per year in the United States [1]. Also, it was reported that idiopathic carpal tunnel syndrome affects up to 1% of the general population and that surgical treatment continues to be the most effective treatment for this condition [2].…”
Section: Introductionmentioning
confidence: 99%